2017
DOI: 10.2106/jbjs.16.00125
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Five-Year Outcomes with Porous Tantalum Acetabular Cup and Augment Construct in Complex Revision Total Hip Arthroplasty

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(112 citation statements)
references
References 20 publications
6
96
0
4
Order By: Relevance
“…In the present study, the postoperative COR were significantly lower compared to the preoperative COR, more close to the anatomic COR ( Table 3). The hip biomechanics were therefore improved, which is consistent with previous reports [15]. Restoration of the COR helps decrease leg length discrepancy and avoid increasing the lever arm, which acts on the head/neck taper caused by increased neck length [11].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…In the present study, the postoperative COR were significantly lower compared to the preoperative COR, more close to the anatomic COR ( Table 3). The hip biomechanics were therefore improved, which is consistent with previous reports [15]. Restoration of the COR helps decrease leg length discrepancy and avoid increasing the lever arm, which acts on the head/neck taper caused by increased neck length [11].…”
Section: Discussionsupporting
confidence: 87%
“…Despite this, very few studies have reported the classifications of augment reconstructions in the superior acetabular area. Derek et al reported [5][6][7][8][9][10][11][12] year follow-up of 85 revision THA cases with porous metal augments and classified the use of slope augments in the superior aspect into the three types, namely "flying buttress", "dome" and "footing" [15]. This classification is not contradictory to the concept of iliac extended fixation, as the essence of extended fixation is the bridging of bone defects via augments to establish a supportive superior point; any augment configuration can be used as long as mechanical stability and anatomical COR are achieved.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations